IMPLICAÇÕES TEÓRICO-PRÁTICAS DO ESTÁGIO NÃO OBRIGATÓRIO NA FORMAÇÃO DO PEDAGOGO: A leitura dos discentes do curso de pedagogia formados na UFMS/CPTL em 2019 - Felipe de Lima Silva (2022)
This master's research carried out within the scope of the Master's in Education at the Federal University of Mato Grosso do Sul, Três Lagoas campus considers the non-mandatory internship, citizen activity added to the course load, a theoretical activity that has become popular in undergraduate courses as it directly interferes in the quality of life of students who manage to reconcile training with work within their training area, linking theory with daily practice. In the pedagogy course, for example, it enables the future teacher's involvement with teaching practices, in a broader period when compared to other formation practices. This important theoretical activity must be analyzed not only from a formative point of view, but also from the perspective of the world of work and the relationships that are established during the time in which the higher education student remains immersed in this educational space, but also in the market in which it will be inserted. Based on these allegations, this research aims to understand the theoretical and practical impact of the Non-Mandatory Internship in the process of teacher education, based on the experience of students from the Pedagogy Course at the Federal University of Mato Grosso do Sul (UFMS) , Três Lagoas Campus (CPTL) formed in the year 2019 and that act/acted in education during the years 2020/2021 defining as specific objectives of this research: identify the formative nature of the non-mandatory internship experience during the pedagogue formation process, elucidate the potential impact of non-mandatory internship on theoretical-methodological formation proposals and analyze the contribution of non-mandatory internship in the construction of this professional's teaching practices. Taking a qualitative approach, the field research is based on references in the field of internship and teacher formation as well as decrees and laws on the subject, understanding the non-mandatory internship (ENO) as a theoretical activity that has relationships between dominant subjects (institutions , universities, integrative agents) and the dominated (students in training) generating practices and learning processes that become an important instrument for understanding the theme as a formation differential. For a reflection on an empirical framework, the semi-structured interview was also adopted, carried out with 9 pedagogues trained in 2019 by UFMS/CPTL, with content analysis as a technique that develops on top of the two aprioristic categories, the first established from the considerations about the historical process of the theme and the second based on the state of knowledge of the ENO carried out in the period 2015-2020. With the categories and interviews, the effect of the non-mandatory internship on the training of these basic education professionals is elucidated from the verbalization of the interviewees.